2007
DOI: 10.1210/en.2007-0476
|View full text |Cite
|
Sign up to set email alerts
|

Rho Guanosine 5′-Triphosphatases Differentially Regulate Insulin-Like Growth Factor I (IGF-I) Receptor-Dependent and -Independent Actions of IGF-II on Human Trophoblast Migration

Abstract: Both IGF-I and IGF-II stimulate migration of human extravillous trophoblast (EVT) cells. Although IGF-I is known to signal through IGF type 1 receptor (IGF1R), IGF-II signals through IGF1R as well as in an IGF1R-independent manner. The purpose of this study was to investigate the roles of Rho GTPases in IGF1R-independent and -dependent actions of IGF-II on EVT cell migration. To distinguish IGF1R-dependent and -independent actions, we used picropodophyllin, a selective inhibitor of IGF1R tyrosine kinase, and I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 45 publications
1
13
0
1
Order By: Relevance
“…1B), but the addition of these compounds did not restore their migratory abilities, suggesting again that RAC1 is an important mediator of PGE 2 -induced migration. In our previous report, we have documented successful knockdown of RAC1 protein following the same siRNA transfection of HTR-8/SVneo cells following 48 h posttransfection [33]. In the present study, we show that knockdown of RAC1 protein remains even 96 h posttransfection (Fig.…”
Section: Rac1 Inhibition Reduces Pge 2 -Induced Migration Of Evt Cellssupporting
confidence: 81%
“…1B), but the addition of these compounds did not restore their migratory abilities, suggesting again that RAC1 is an important mediator of PGE 2 -induced migration. In our previous report, we have documented successful knockdown of RAC1 protein following the same siRNA transfection of HTR-8/SVneo cells following 48 h posttransfection [33]. In the present study, we show that knockdown of RAC1 protein remains even 96 h posttransfection (Fig.…”
Section: Rac1 Inhibition Reduces Pge 2 -Induced Migration Of Evt Cellssupporting
confidence: 81%
“…PPP inhibits activity of IGF-1R Vasilcanu et al, 2004Vasilcanu et al, , 2006Ulfarsson et al, 2005;Strömberg et al, 2006;Colón et al, 2007;Conti et al, 2007;Guha et al, 2007;Razuvaev et al, 2007;Shields et al, 2007) but also down-regulates the receptor (Vasilcanu et al, 2008). Even though PPP may have other effects, we conclude that it does not cross-target the highly homologous insulin receptor .…”
mentioning
confidence: 67%
“…We and others demonstrated that PPP is an inhibitor of the IGF-1R tyrosine phosphorylation Colón et al, 2007;Conti et al, 2007;Shields et al, 2007). In contrast, PPP did not inhibit the tyrosine kinase activity of insulin receptor or other major cancer-relevant growth factor receptors .…”
mentioning
confidence: 71%
“…In addition, extremely small (less than 1.5-fold) but statistically significant differences in Rhoa (higher in leptin) and Rock2 (higher in control) were seen at 1 h, suggesting dynamic regulation of this pathway by leptin, but not a specific direction of change. Both RHOA and RHOC are involved in control of focal adhesion and cell motility in many cell types, including human extravillous trophoblasts [41]. In addition, both MAP2K1 (MEK) and rho-dependent kinase activity have been implicated in leptin stimulation of invasion in cancer cells [42].…”
mentioning
confidence: 99%